Educators’ Readiness in using Mobile Phone as a Pedagogical Tool for Teaching - Nur’ain Hamsan, Siti; Abdul Aziz, Maslina; Taslim, Jamaliah (International Journal of Engineering and Technology, 2018)
Owing to the rapid growth of technology, higher educational institutions are looking for new learning systems. One of the evolutions of classroom technology is using mobile phone for teaching-learning or m-learning. The use of mobile phone in classroom is still new in Malaysia. Therefore, this research aims to study educatorsâ€™ readiness in integrating mobile technology in the teaching process. The objective of this study is to identify the level of technology readiness among educators in higher education institutions towards the implementation of mobile phone as pedagogical tools in the teaching and learning process. Besides that, this study identifies the relationship between the dimensions of technology belief and educatorâ€™ readiness. In order to achieve this objective, quantitative approach and questionnaire instrument are used to gather data from the respondents. This study adopts Parasuramanâ€™s study on Technology Readiness Index (TRI). The findings show that there is a high level of technology readiness among educators with a positive and significant relationship between the dimensions of technology belief and educatorsâ€™ readiness with optimism as the main influencer. The findings from this research may provide some key consideration to the higher education institutions to determine the greatest solution in ensuring the successful of m-learning post-implementation.Â